Aid effectiveness and capacity development: Implications for economic growth in developing countries - Sanyal, Prabuddha; Babu, Suresh Chandra (Scientific Research Publishing, Inc., 2012)
In this paper, we present a stylized model for understanding the relationship between capacity strengthening and eco-nomic growth in an endogenous growth framework. Endogenous growth theory provides a novel starting point for combining individual, organizational, and enabling environmental issues as part of attaining the capacity-strengthening goal. Our results indicate that although donors can play an important role in aiding countries to develop their existing capacities or to generate new ones, under certain conditions, the potential also exists for uncoordinated and fragmented donor activities to erode country capacities. From the policy exercises, we demonstrate that improving economy-wide learning unambiguously increases the rate of growth of output, technology, capital stock, and capacity. Moreover, a donor’s intervention has the maximum impact on the above variables when the economy’s capacity is relatively low. In contrast, donor intervention can lead to “crowding-out effects” when the economy’s capacity is moderately high. Under such a situation, the economy never reaches a new steady state. Our results not only lend support to diminishing returns to aid but also to an S model of development aid and country capacity relationship.